PERAN BUDAYA ORGANISASI DALAM MENINGKATKAN PRESTASI KERJA STAF ORGANISASI WIJABA - Fatchurrohman, Mochamad; Nafiqoh, Anin (JURNAL KINDAI, 2024)
The aim of the research is to explain the role of organizational culture in improving the work performance of WIJABA organizational staff. The research design used in this research is a qualitative method. Going through several stages of observation, requesting permission for the author to research, and conducting interviews. The data source was obtained from primary data through field research, namely interviews with division managers within WIJABA a. The research results show: (1) organizational culture is a habit or behavior that develops from the beginning and is passed down from generation to generation in a community or group so that it continues until there are new members and so on. (2) work performance is the achievement achieved by each individual or team where the achievement has achieved or even exceeded the given target. (3) the role of organizational culture in improving work performance, namely: staff need to improve and develop new innovations, well-maintained communication skills influence leader trust. Therefore, it is important to have weekly meetings to find out the progress of each staff. Keywords: Organizational Culture, Job Performance, Organization Staff, Wijaba